Epidemiology and Prognosis of Invasive Fungal Disease in Chinese Lung Transplant Recipients - Ju, Chunrong; Lian, Qiaoyan; Xu, Xin; Cao, Qingdong; Lan, Cong; Chen, Rongchang; He, Jianxing (Frontiers in Medicine, 2021)
This study explored the epidemiology, risk factors, and prognosis of invasive fungal disease (IFD) in Chinese lung transplant recipients (LTRs). This retrospective cohort study included patients who received lung transplants at four hospitals in South China between January 2015 and June 2019. The participants were divided into IFD and non-IFD (NIFD) groups. The final analysis included 226 LTRs (83.2% males) aged 55.0 ± 14.2 years old. Eighty-two LTRs (36.3%) developed IFD (proven or probable diagnosis). The most common pathogens were Aspergillus (57.3%), Candida (19.5%), and Pneumocystis jiroveci (13.4%). Multivariate logistic regression revealed that anastomotic disease [odds ratio (OR): 11.86; 95% confidence interval (95%CI): 4.76–29.54; P < 0.001], cytomegalovirus (CMV) pneumonia (OR: 3.85; 95%CI: 1.88–7.91; P = 0.018), and pre-transplantation IFD (OR: 7.65; 95%CI: 2.55–22.96; P < 0.001) were associated with higher odds of IFD, while double-lung transplantation (OR: 0.40; 95%CI: 0.19–0.79; P = 0.009) was associated with lower odds of IFD. Logistic regression analysis showed that anastomotic disease was associated with higher odds of death (OR: 5.01; 95%CI: 1.24–20.20; P = 0.02) and that PJP prophylaxis was associated with lower odds of death (OR: 0.01; 95%CI: 0.001–0.11; P < 0.001). Invasive fungal disease is prevalent among LTRs in southern China, with Aspergillus the most common pathogen. Prophylaxis should be optimized based on likely pathogens.